2023
DOI: 10.1177/09612033231153791
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the EULAR/ACR classification criteria and organ damage in systemic lupus erythematosus

Abstract: Objectives To study the relationship between the 2019 EULAR/ACR classification criteria and organ damage in patients with systemic lupus erythematosus (SLE). Methods Patients involved in a cross-sectional validation study of the EULAR/ACR criteria and judged by a panel of rheumatologists to be clinical SLE were studied. Those who fulfilled the EULAR/ACR criteria at their last clinic visit were stratified into 2 groups based on a cutoff score of 20. The last SLE International Collaborating Clinic (SLICC) Organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
2
1
2
Order By: Relevance
“…In contrast to the results from Chi Chiu Mok et al, 1 we found that the EULAR/ACR score at diagnosis was predictive for damage accrual in the following 10 years. Our study was powered by a higher number of participants which could explain this discrepancy in results (867 vs 251 participants in the analysis).…”
contrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to the results from Chi Chiu Mok et al, 1 we found that the EULAR/ACR score at diagnosis was predictive for damage accrual in the following 10 years. Our study was powered by a higher number of participants which could explain this discrepancy in results (867 vs 251 participants in the analysis).…”
contrasting
confidence: 99%
“…These results were corroborated by multivariable regression analysis, patients with the higher score had a 40% increased risk of developing damage (HR 1.40, p = 0.002), and the risk persisted even when analyzing the subgroup of patients without lupus nephritis (HR 1.46, 0 = 0.006). 4 In contrast to the results from Chi Chiu Mok et al, 1 we found that the EULAR/ACR score at diagnosis was predictive for damage accrual in the following 10 years. Our study was powered by a higher number of participants which could explain this discrepancy in results (867 vs 251 participants in the analysis).…”
contrasting
confidence: 99%
See 3 more Smart Citations